A meta‐analysis on the trust in agrifood supply chains. Issue 3 (15th February 2022) - Assis, Michel T. Q. M.; Lucas, Maria Raquel; Rainho, Maria José M.
Abstract: The agrifood literature suggests that trust is one of the most prominent and critical aspect for not only the effectiveness of collaboration, but also for improving sustainability performance. In this sense, the understanding of how trust works in agrifood supply chains is essential to find better paths to improve the functioning of those structures. The purpose of this article was to carry out a meta‐analysis on the relationships of trust among the stakeholders in agrifood supply chains, to obtain data on previous publications as well as to justify future research on the search topics. For the bibliometric study, the R software in RStudio and the R packages bibliometrix and biblioshiny were used. The documents were extracted from the Scopus and Web of Science databases. Documents related to the researched topics, that were published in the last 11 years, were collected to the following meta‐analysis. Of 277 documents published from 1995 to 2021, 11 review articles and 74 papers were analyzed. From these publications, we obtained data on the main authors and sources related to trust among the stakeholders in agrifood supply chains, on the methodologies used, as well as on trends for future researches. The present work brings forward data in a unique and up‐to‐date way.